Typology of production units and livestock technologies for adaptation to drought in Sinaloa, Mexico - Cuevas-Reyes, Venancio; Loaiza, Alfredo; Gutiérrez, Obed; Buendía, Germán; Rosales-Nieto, Cesar (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Drought as an effect of climate change affects the productivity and sustainability of livestock systems. The objective of this study was to analyze how technological land management for adaptation to climate change adopted by livestock farmers in southern Sinaloa, Mexico, corresponds to the typologies identified in the study area. A non-probabilistic sampling was applied, selecting 50 production units (UP) in six municipalities of Sinaloa, whose information was analyzed by cluster analysis and descriptive statistics. It was identified three livestock typologies. Cluster 1 (46 %), was defined as subsistence since its production units (PU) have few animals and showed the smallest total surface area, the producers are the oldest and use the shade in paddocks and the adjustment of stocking rates as drought mitigation practices. Cluster 2 (46 %), showed the medium productive behavior, conformed by younger producers whose PU showed a larger area of crops and rangeland, this group adopted stocking rate adjustment, forage conservation and species diversification as mitigation measures. Cluster 3 (8 %) showed the highest total area, livestock inventory and productivity levels; drought mitigation decisions are focused on stocking rate adjustment and forage conservation. The study identified mitigation practices related to land use from the farmers’ point of view. These results can be used to conduct studies in similar environments and to scale adaptation measures for climate change from the local level and by type of farmer